2020
DOI: 10.1016/j.celrep.2020.107703
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Splicing Program Ensures Proper Synaptic Connections in the Developing Cerebellum

Abstract: Highlights d A dynamic splicing program shapes the cerebellar transcriptome during development d Autism-spectrum-disorder-related genes exhibit developmental splicing regulation d Sam68 establishes a splicing signature that ensures proper synaptic maturation d Sam68 regulates genes associated with autism spectrum disorder and social behavior

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 79 publications
0
65
0
Order By: Relevance
“…Sam68 is well known for its role in the regulation of alternative splicing ( Frisone et al, 2015 ). Several studies have identified Sam68 target genes that are involved in synaptic transmission, metabolism, and apoptosis ( Paronetto et al, 2007 , 2011 ; Iijima et al, 2011 ; La Rosa et al, 2016 ; Farini et al, 2020 ), which may underlie the motor neuron defects observed in our study. Changes in the splicing outcome of the tomosyn-2 gene ( Stxbp5l ) are particularly relevant for the phenotype.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Sam68 is well known for its role in the regulation of alternative splicing ( Frisone et al, 2015 ). Several studies have identified Sam68 target genes that are involved in synaptic transmission, metabolism, and apoptosis ( Paronetto et al, 2007 , 2011 ; Iijima et al, 2011 ; La Rosa et al, 2016 ; Farini et al, 2020 ), which may underlie the motor neuron defects observed in our study. Changes in the splicing outcome of the tomosyn-2 gene ( Stxbp5l ) are particularly relevant for the phenotype.…”
Section: Discussionmentioning
confidence: 68%
“…Previous work indicated that Sam68 is highly expressed in the motor neurons of the spinal cord ( Pagliarini et al, 2015 ), suggesting an important function of this protein in these cells. Sam68 is known to modulate splicing of several genes encoding for synaptic proteins ( Iijima et al, 2011 ; Danilenko et al, 2017 ; Witte et al, 2019 ; Farini et al, 2020 ). To test whether Sam68 regulates splicing of such synaptic genes in the spinal cord, we selected splicing events from several RNA-sequencing and microarray experiments carried out in Sam68-depleted mouse tissues or cells ( Ehrmann et al, 2008 ; Chawla et al, 2009 ; Iijima et al, 2011 ; Paronetto et al, 2011 ; La Rosa et al, 2016 ; Danilenko et al, 2017 ; Witte et al, 2019 ; Farini et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations